Identification of Populus Small RNAs Responsive to Mutualistic Interactions With Mycorrhizal Fungi, Laccaria bicolor and Rhizophagus irregularis - Mewalal, Ritesh; Yin, Hengfu; Hu, Rongbin; Jawdy, Sara; Vion, Patrice; Tuskan, Gerald A.; Le Tacon, François; Labbé, Jessy L.; Yang, Xiaohan (Frontiers in Microbiology, 2019)
Ecto- and endo-mycorrhizal colonization of Populus roots have a positive impact on the overall tree health and growth. A complete molecular understanding of these interactions will have important implications for increasing agricultural or forestry sustainability using plant:microbe-based strategies. These beneficial associations entail extensive morphological changes orchestrated by the genetic reprogramming in both organisms. In this study, we performed a comparative analysis of two Populus species (Populus deltoides and P. trichocarpa) that were colonized by either an arbuscular mycorrhizal fungus (AmF), Rhizophagus irregularis or an ectomycorrhizal fungus (EmF), Laccaria bicolor, to describe the small RNA (sRNA) landscape including small open reading frames (sORFs) and micro RNAs (miRNAs) involved in these mutualistic interactions. We identified differential expression of sRNAs that were, to a large extent, 1) within the genomic regions lacking annotated genes in the Populus genome and 2) distinct for each fungal interaction. These sRNAs may be a source of novel sORFs within a genome, and in this regard, we identified potential sORFs encoded by the sRNAs. We predicted a higher number of differentially-expressed miRNAs in P. trichocarpa (4 times more) than in P. deltoides (conserved and novel). In addition, 44 miRNAs were common in P. trichocarpa between the EmF and AmF treatments, and only 4 miRNAs were common in P. deltoides between the treatments. Root colonization by either fungus was more effective in P. trichocarpa than in P. deltoides, thus the relatively few differentially-expressed miRNAs predicted in P. deltoides might reflect the extent of the symbiosis. Finally, we predicted several genes targets for the plant miRNAs identified here, including potential fungal gene targets. Our findings shed light on additional molecular tiers with a role in Populus-fungal mutualistic associations and provides a set of potential molecular targets for future enhancement.